Reliability of muscle strength measures obtained with a hand‐held dynamometer in an elderly population - Buckinx, Fanny; Croisier, Jean‐Louis; Reginster, Jean‐Yves; Dardenne, Nadia; Beaudart, Charlotte; Slomian, Justine; Leonard, Sylvain; Bruyère, Olivier (Clinical physiology and functional imaging, 2017)
Summary Background The objective of this study was to assess the reliability of a hand‐held dynamometer for isometric strength measurements among nursing home residents. Methods The isometric muscle strength of nursing home residents was assessed for eight different muscle groups, using a hand‐held dynamometer, the MicroFET2 device. Strength measurements were performed at baseline and after 4 days by the same operator and after 8 days by a second operator. Intraclass coefficients (ICC) were computed to assess the relative reliability, whereas the minimal detectable change (MDC%) was calculated to assess the absolute reliability of the test–retest of the MicroFET2 used by one single operator or by two different ones. Results Thirty nursing home residents (75·0 ± 11·2 years, 50% of women) were enrolled in this study. ICC of the test–retest with one single operator ranged from 0·60 (0·37–0·83) for the ankle extensors to 0·85 (0·74–0·95) for the elbow flexors. When considering the test–retest with two different operators, the ICC values ranged from 0·62 (0·41–0·84) for the ankle extensors to 0·87 (0·79–0·96) for the elbow extensors. For the absolute reliability, MDC% varies from 27·64 (elbow flexors) to 81·97 (ankle extensors) when performed in intra‐observer. In interobserver condition, MDC%, respectively, varies from 24·38 (elbow extensors) 67·59 (ankle extensors). Conclusion Using standardized protocol and standardized instructions to patients, a high relative and moderate absolute reliability was observed for all but ankle muscle groups, making this hand‐held dynamometer a potential tool for research in the elderly population.